2013
DOI: 10.5812/ircmj.10157
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus Seropositivity in Nurses and Paramedical Personnel at a University Hospital in North Iran

Abstract: BackgroundThe status of hepatitis A virus (HAV) among health care workers has not been studied yet in Iran.ObjectivesThis study aimed to evaluate the HAV seropositivity among the healthcare personnel in Ayatollah Rohani Hospital, Babol, Iran, according to age, number of working years, and other demographic data.Patients and MethodsThis cross sectional study was performed on all nurses, nurses' aid, and paramedical technicians at Ayatollah Rohani Hospital, Babol, from March 2011 to March 2012. Blood was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Bayani ve ark. 'nın İran'da hastane personelinde yaptıkları çalışmada antiHBs seropozitifliği %71 olarak tespit edilmiş, cinsiyetler arasında istatistiksel olarak bir fark bulunmamıştır (26).…”
Section: Introductionunclassified
“…Bayani ve ark. 'nın İran'da hastane personelinde yaptıkları çalışmada antiHBs seropozitifliği %71 olarak tespit edilmiş, cinsiyetler arasında istatistiksel olarak bir fark bulunmamıştır (26).…”
Section: Introductionunclassified
“…However, about 30% of healthcare personnel are not immuned against HAV and in exposure with HAV infected patients and need confident preventive strategy. As conclusion of this project, role of vaccination program in protecting susceptible HCWs should be more highlighted ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bayani et al ( 1 ) reported the significantly increase in sero-prevalence with age, 77.4% for 30-39 years and 85.3% for more than 40 years. less prevalence in lower age has confirmed in other studies in general populations from different parts of Iran ( 5 ).…”
mentioning
confidence: 97%
“…I read with interest the published article by Bayani et al ( 1 ) in your esteemed journal recently. The topic is important for health policy makers to find better view regarding epidemiology of hepatitis A virus (HAV) infection in the community.…”
mentioning
confidence: 98%
See 1 more Smart Citation